Um estudo das personagens femininas em Autran Dourado - Perna Filho, Francisco (2018)
This is a critical study of the work of Autran Dourado, focusing on the construction of the female characters in his novels and novellas, more specifically in the five books that compose the corpus of this work: The Ship of Men (1961), A Hidden Life (1964), The Voices of the Dead (1967), The Death Knoll (1974), and Donga Novais’ Story Book (1976), whose protagonists are, respectively: Maria, Biela, Rosalina, Malvina and Lelena, adding to them the secondary characters, those who are ex-centric and marginal, as fundamental to the structure of those narratives. As the focus of this work is related to the construction of the female characters, more precisely on the way in which women are represented in Autran Dourado’s works, a wide range of theoretical works on gender, eroticism, memory and metalanguage, were chosen as support basis for what is here analyzed. Firstly, we sought to draw the presentation, representation and memory of each selected main character, according to the chronological sequence of writing and publication of the novels. Chapter 1 presents a more descriptive analysis of those female characters and Chapter 2 presents an analysis based on the themes and problems of love and sexuality. Through these analyses, the representation of the feminine in Autran Dourado is discussed as constituting significant advance and progress, even when the writer reproduces some gender conditions of the time, regarding the practice of love and sexuality, through which the women represented by the protagonist characters become autonomous, acquire determination and is allowed to really live, to realize herself in fullness. To complete the analysis of these leading characters, a sub-chapter has become necessary to deal with the prostitutes, the marginal characters, essential to establish the counterpoint with the women from the “upper” or the wealthy class – it is in this part, specifically, that it was necessary to bring the novel Pattern for a Tapestry (1970) into the analysis. In Chapter 3, the last one, the focus is directed upon the ex-centric and marginal characters (HUTCHEON, 1991). For this analysis and from three of the books which constitute the corpus of this work, The Death Knoll, The Voices of the Dead, and The Ship of Men, in this order, not considering the date of writing and publication of the books, but the fictional period in which they are set, we have selected the following characters: Inacia, Quiquina and Luzia, to be studied as a counterpoint to the protagonists, their white, high caste and powerful mistresses. This study concludes with the certainty that the female characters in the novels by of Autran Dourado (at least in the novels here discussed), go beyond been simple narrative functions, characterizing themselves as a symbolic example of a new woman.